PENGARUH KUALITAS LAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN KONTER RIDHO CELL KOTA BEKASI - Widya Puspita Sari; Arry Dwi Syahputra (Jurnal Ekonomi dan Industri, 2024)
This research aims to analyze the influence of service quality and price on customer satisfaction at the Bekasi City Ridho Cell counter. The population of this research is Ridho Cell counter customers in Bekasi City. The research was carried out by distributing questionnaires to Ridho Cell counter customers in Bekasi City. The data analysis method uses simultaneous and partially linear regression analysis. The results of this research show that simultaneous and partially service quality and price have a positive and significant effect on customer satisfaction at the Bekasi City Ridho Cell counter.